“Langkah Tanpa Suara” Interpretasi Dari Kegigihan Seseorang Tunarungu Dalam Kehidupan - Sari, Rohima; Rovylendes, Adjuoktoza; Loravianti, Susas Rita; Ilham, Kurniadi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The dance piece entitled Langkah Tanpa Suara is inspired by the lived experience of a deaf individual confronting limitations in verbal communication. This work serves as an artistic expression of the resilience and determination exhibited by this person in navigating life, despite often being underestimated by society. The creative process employed data collection and field observation to gain insight into the lives of the deaf community, followed by movement exploration and improvisation as foundational steps; the development of choreographic structure; and periodic evaluation. Technically, the work is performed by seven dancers and features a socially driven, dramatic theme. The narrative is enhanced through the incorporation of sequenced music that aligns with the movement progression, thereby enriching the emotional and dramatic expressiveness of the performance.